Weaning transition, but not the administration of probiotic candidate Kazachstania slooffiae, shaped the gastrointestinal bacterial and fungal communities in nursery piglets - Harlow, KaLynn; Summers, Katie Lynn; Oliver, William T.; Wells, James E.; Crouse, Matthew; Neville, Bryan W.; Rempel, Lea A.; Rivera, Israel; Ramsay, Timothy G.; Davies, Cary Pirone (Frontiers in Veterinary Science, 2024)
As in-feed antibiotics are phased out of swine production, producers are seeking alternatives to facilitate improvements in growth typically seen from this previously common feed additive. Kazachstania slooffiae is a prominent commensal fungus in the swine gut that peaks in relative abundance shortly after weaning and has beneficial interactions with other bacteriome members important for piglet health. In this study, piglets were supplemented with K. slooffiae to characterize responses in piglet health as well as fungal and bacterial components of the microbiome both spatially (along the entire gastrointestinal tract and feces) and temporally (before, during, and after weaning). Litters were assigned to one of four treatments: no K. slooffiae (CONT); one dose of K. slooffiae seven days before weaning (day 14; PRE); one dose of K. slooffiae at weaning (day 21; POST); or one dose of K. slooffiae seven days before weaning and one dose at weaning (PREPOST). The bacteriome and mycobiome were analyzed from fecal samples collected from all piglets at day 14, day 21, and day 49, and from organ samples along the gastrointestinal (GI) tract at day 21 and day 49. Blood samples were taken at day 14 and day 49 for cytokine analysis, and fecal samples were assayed for antimicrobial resistance. While some regional shifts were seen in response to K. slooffiae administration in the mycobiome of the GI organ tractmycobiome, no remarkable changes in weight gain or health of the animals were observed, and changes were more likely due to sow and the environment. Ultimately, the combined microbiome changed most considerably following the transition from suckling to nursery diets. This work describes the mycobiome along the piglet GI tract organ mycobiome through the weaning transition for the first time. Based on these findings, K. slooffiae administered at this concentration may not be an effective tool to hasten colonization of K. slooffiae in the piglet GI tract around the weaning transition nor support piglet growth, microbial gut health, or immunity. However, diet and environment greatly influence microbial community development.